(untitled) (Acta Scientiarum. Agronomy, 2014)
The purpose of this study was to evaluate the effects of light restriction on the growth of benghal dayflower (Commelina benghalensis). The experiment was conducted in pots under full sunlight and with 18.5, 30, 40, 50, 60 and 70% artificial light restriction treatments. Plant growth was evaluated up to 90 days after planting (DAP), and mathematical models of the major shoot length, internode length, individual area of the first leaf completely expanded, number of leaves and shoot and root dry mass weights were established depending on increasing light restriction levels. The elevation of the light gradient promoted reductions in the number of leaves and fasciculate root dry mass weight. Light restriction did not induce alterations in the plasticity of performance (alterations in total biomass accumulation) of the C. benghalensis plants, the stability of which was related to an integration of the expected morphological, anatomical and physiological adjustments, constituting in a strong evidence of shading tolerance.